2018
DOI: 10.20344/amp.9817
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Ageing in Portugal: Data from the EpiDoC Cohort

Abstract: RESUMOIntrodução: A esperança de vida está a aumentar em Portugal, contudo desconhece-se o estado de saúde dos idosos. Pretende-se determinar a prevalência de multimorbilidade, caracterizar estilos de vida e outros fatores relacionados com a saúde dos idosos. Material e Métodos: Efetuou-se uma avaliação transversal a 2393 adultos com 65 ou mais anos de idade, da coorte EpiDoC que é constituída por uma amostra representativa da população portuguesa. Os inquiridos responderam a um questionário estruturado atravé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 30 publications
9
54
0
2
Order By: Relevance
“…Our study revealed a mean LOS of 10.6 days and a median of 8 days which was in line with other reports [3,29,34]. Eventual differences between studies and countries are related to the availability of continuing care outside the hospital environment [41].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study revealed a mean LOS of 10.6 days and a median of 8 days which was in line with other reports [3,29,34]. Eventual differences between studies and countries are related to the availability of continuing care outside the hospital environment [41].…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed a sex gap, with men presenting higher numbers of CAP hospitalizations, mortality and a higher risk of death during hospitalization. These results are in accordance with other studies that show a sex inequality in health indicators associated with hospitalizations [3,4,12,29], with men presenting consistently higher hospitalization rates for CAP, which may be related to a great number of risk factors, such as smoking, alcoholism, and exposure to toxic occupational exposure [3,29]. The greater ratio of male to female mortality may also reflect higher rates of smoking in males predisposing to respiratory disease [3,16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The favourable results found among the Portuguese do not seem to be explained, however, by their pro le, since their demographic and health data are similar to those of Brazilians, with the number of participants incidentally close in relation to diseases. This fact possibly results from the pairing between the groups carried out in the methodological path of our research, which is similar to that of other studies carried out in Portugal, where high rates of comorbidities were observed in addition to frequent depressive symptoms and obesity (31) . However, it is noteworthy that Brazil and Portugal are countries with very different levels of economic development, which can lead to an important comparison bias from an economic and social point of view (15,16) .…”
Section: Discussionsupporting
confidence: 85%
“…Low Internet usage is due in part to lower education levels of older European citizens in these countries. In Portugal, for example, 77.3% of individuals over 65 years old have 4 or less years of education, and 84.5% have never used computers, videogames, or tablets ( 41 ). The “Blueprint” initiative, which aims to implement prevention programmes among European older adults, will, therefore, take significant time (e.g., 5–10 years) to implement among elderly EU citizens.…”
Section: Occupational Perspective On Active Ageingmentioning
confidence: 99%